Polska Partia Robotnicza w powiecie ostrołęckim w latach 1945-1948 - FIOŁEK, Damian (Historia i Świat, 2017)
The aim of the publication is to present the research conducted by history students at the Siedlce University. "Polish Workers’ Party in Ostrołęka County in 1945-1948" is an extended abstract of BA thesis.